PONM22 An investigation into the diagnosis and further management of chronic idiopathic polyneuropathies. Issue 11 (22nd October 2010) - Stevens, K; Reilly, M; Almemar, A
Abstract : Background: Approximately 20% of all patients referred for the investigation of peripheral neuropathy will remain idiopathic despite extensive and expensive investigative tests. There have been no studies comparing the practice of peripheral nerve or neuromuscular specialists with general neurologists and neurology trainees in the diagnostic work up and further management of this condition. Methods: We used an online questionnaire comprising of 13 questions. Specialists were taken as those running a specialist clinic or members of the British Peripheral Nerve Society (BPNS). The questionnaire was disseminated via the ABN newsletter and hospital administrative staff. Results: 59 Participants: 12 BPNS members, 36 consultant neurologists, 10 ABN Trainees. 100% of trainees, 86.1% of general neurologists and 54% of BPNS members would continue to investigate someone with a polyneuropathy despite a clear cause such as renal failure or excess alcohol being evident on history or examination. Only 12/38 who responded to the question on functional scoring routinely used a functional score. 18/59 responded to the question on trial of therapy, of which 11/18 would consider IVIG and 8/18, a trial of steroids, in all cases this would only be for rapidly progressive symptoms. Conclusions: The majority of clinicians do not routinely use a functional score. The rationale behind investigations was similar in all three groups. There are a significant minority of clinicians from all groups who will consider a trial of therapy—either IVIG or steroids—for rapidly progressive symptoms. Though only a small number in the survey, it appears as if BPNS members were more specific with their investigations, and junior ABN trainees the most likely to carry out investigations. Further Work: Increase numbers participating in survey to see if trends are significant. Assess whether implementing a diagnostic guideline would affect discrepancies between specialists and nonspecialists as well as overall number of investigations requested.